Pharmacological effects of ex vivo mesenchymal stem cell immunotherapy in patients with acute kidney injury and underlying systemic inflammation. (28th September 2021) - Swaminathan, Madhav; Kopyt, Nelson; Atta, Mohamed G.; Radhakrishnan, Jai; Umanath, Kausik; Nguyen, Sunny; O'Rourke, Brian; Allen, Ashley; Vaninov, Natalie; Tilles, Arno; LaPointe, Elizabeth; Blair, Andrew; et al.
Abstract: Mesenchymal stem cells (MSCs) have natural immunoregulatory functions that have been explored for medicinal use as a cell therapy with limited success. A phase Ib study was conducted to evaluate the safety and immunoregulatory mechanism of action of MSCs using a novel ex vivo product (SBI‐101) to preserve cell activity in patients with severe acute kidney injury. Pharmacological data demonstrated MSC‐secreted factor activity that was associated with anti‐inflammatory signatures in the molecular and cellular profiling of patient blood. Systems biology analysis captured multicompartment effects consistent with immune reprogramming and kidney tissue repair. Although the study was not powered for clinical efficacy, these results are supportive of the therapeutic hypothesis, namely, that treatment with SBI‐101 elicits an immunotherapeutic response that triggers an accelerated phenotypic switch from tissue injury to tissue repair. Ex vivo administration of MSCs, with increased power of testing, is a potential new biological delivery paradigm that assures sustained MSC activity and immunomodulation. Abstract : Mesenchymal stem cells (MSCs) have natural immunoregulatory functions that have been explored for medicinal use as a cell therapy with limited success. A phase 1b study was conducted to evaluate the safety and immunoregulatory mechanism of action of MSCs using a novel ex vivo product (SBI‐101) to preserve cell activity in patients with severe acute kidney injury (AKI).